2020
DOI: 10.1037/pha0000350
|View full text |Cite
|
Sign up to set email alerts
|

Investigating tobacco withdrawal in response to reduced nicotine cigarettes among smokers with opioid use disorder and other vulnerabilities.

Abstract: Individuals with opioid use disorder (OUD) have high prevalence of smoking and poor cessation outcomes. Data suggest that smokers with OUD may experience heightened nicotine reinforcement and more severe tobacco withdrawal compared to smokers without OUD. The Food and Drug Administration is currently considering reducing the nicotine content of cigarettes to reduce smoking prevalence and smoking-related disease. It is critical to understand the effects of reduced nicotine content cigarettes (RNCCs) on tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Prior research has shown that elevated depression symptoms associated with greater cigarette withdrawal during a past quit attempt reported retrospectively (Tsoh et al, 2003), measured across 3 days of biochemically verified abstinence (Pomerleau et al, 2005), and in response to reduced nicotine cigarettes (Streck et al, 2020). The current study extends these findings by suggesting that people with elevated depression symptoms who smoke may experience elevated withdrawal during periods of both abstinence and non-abstinence.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Prior research has shown that elevated depression symptoms associated with greater cigarette withdrawal during a past quit attempt reported retrospectively (Tsoh et al, 2003), measured across 3 days of biochemically verified abstinence (Pomerleau et al, 2005), and in response to reduced nicotine cigarettes (Streck et al, 2020). The current study extends these findings by suggesting that people with elevated depression symptoms who smoke may experience elevated withdrawal during periods of both abstinence and non-abstinence.…”
Section: Discussionsupporting
confidence: 67%
“…One laboratory-based study in people with elevated baseline depression symptoms who smoke, found that smoking research cigarettes with varying levels of nicotine following cigarette abstinence associated with greater cigarette withdrawal (Streck et al, 2020). However, this study did not report an effect of depression symptom level on withdrawal when participants smoked their usual brand cigarettes or during periods of non-abstinence (Streck et al, 2020) so these effects may be specific to DEPRESSION, SMOKING, LAB STUDY smoking cigarettes with reduced nicotine levels during abstinence. Another laboratory-based study reported people with elevated depression symptoms who smoke (vs. low depression symptoms) experienced more intense cigarette withdrawal across 3 days of biochemically verified abstinence (Pomerleau et al, 2005), but did not assess withdrawal during nonabstinence.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar analyses on marijuana use suggest that switching to low nicotine cigarettes is likely to benefit people regardless of marijuana use status and is unlikely to alter the prevalence or frequency of cannabis use ( Pacek et al., 2016 ). Finally, nicotine reduction clinical trials enrolling people who use opioids found that this smoking population also experienced lower smoking rates and decreased nicotine dependence severity after using low nicotine cigarettes, relative to normal nicotine cigarettes ( Higgins et al., 2017 , Higgins et al., 2020 ; Streck et al., 2020 ). Overall, evidence does not support that nicotine reduction affects people who use other drugs uniquely, nor that nicotine reduction leads to the compensatory use of other substances.…”
Section: Resultsmentioning
confidence: 99%
“…One study focused on perceptions of five endgame policies (mandating a VLNC standard for tobacco products, setting product standards (removing additives from tobacco), reduced risk products, tobacco tax increases and restrictions on the number of tobacco retailers) among people on a low income in Aotearoa (New Zealand),43 while the remaining 17 studies described the impacts of mandating VLNC for smoked tobacco products to make them non-addictive or minimally addictive among participants based in the USA. The authors of 14 of these 17 studies are affiliated with the same research centre (the Center for Alcohol and Addiction Studies at Brown University in the USA) 44–55…”
Section: Resultsmentioning
confidence: 99%